PENGARUH PEMBERIAN NPK 16:16:16 DAN POC KOHE KAMBING TERHADAP PERTUMBUHAN TANAMAN CABAI (CAPSICUM ANNUM L.) - Surya Fajri; Safruddin Safruddin; Suyatno Suyatno (Smart Education, 2025)
Abstract: Red chili is one of the crops commonly cultivated by farmers in several regions of Indonesia. This is due not only to its high economic value but also to its various health benefits. This study aims to determine the effect of applying different concentrations of NPK 16:16:16 fertilizer and goat manure liquid organic fertilizer (POC Kohe Kambing) on the growth of red chili plants. The experimental design used was a Randomized Block Design (RBD), while the treatment design was factorial, consisting of two factors: NPK 16:16:16 (N) with three treatment doses: N0: 0 ml/plot, N1: 60 g/plot, and N2: 120 g/plot. ,Goat manure liquid organic fertilizer (POC Kohe Kambing) with four levels: P0: 0 liter/plot, P1: 1 liter/plot, P2: 2 liters/plot, and P3: 3 liters/plot, each with three replications. The observed variables included plant height, the height of the first branch, stem base diameter, and the number of leaves. The results showed that the application of different doses had a significant effect on plant height, the height of the first branch, stem base diameter, and the number of leaves across all observation periods. NPK 16:16:16 influenced observations at 56 days after planting. The best results for goat manure liquid organic fertilizer were achieved at P3 (3 liters/plot). The interaction between NPK 16:16:16 doses and goat manure liquid organic fertilizer significantly affected all observed parameters.Â Keywords: Red Chili, NPK 16:16:16 Fertilizer, Goat Manure POC, Plant GrowthAbstrak: Cabai merah merupakan salah satu jenis tanaman yang umumnya ditanam oleh petani di beberapa wilayah di Indonesia. Ini disebabkan tidak hanya oleh tingginya nilai jual cabai merah, tetapi juga karena buah ini memiliki beberapa keuntungan untuk Kesehatan. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian konsentrasi Pupuk NPK 16:16:16 dan POC Kohe Kambing terhadap pertumbuhan tanaman Cabai merah. Rancangan yang digunakan adalah Rancangan Acak Kelompok (RAK), sedangkan rancangan perlakuannya adalah Faktorial, yang terdiri atas dua faktor yang diteliti, yaitu :1. NPK 16:16:16 (N) terdiri dari 3 dosis perlakuan N0: 0ml/plot, N1: 60g/plot, U2: 120g/plot. Dosis yang ke 2. POC KOHE Kambing terdiri dari 4 Taraf P0: 0 liter/plot, P1: 1 lliter/plot, P2: 2 liter/plot, P3: 3 liter/plot dengan 3 ulangan. Peubah amatan yang diamati: Tinggi Tanaman, Tinggi Cabang Pertama, Diameter Pangkal Batang, Jumlah Daun. Hasil penelitian menunjukkan bahwa Aplikasi perbedaan dosis menunjukan pengaruh yang nyata pada pengamatan tinggi tanaman, Tinggi Cabang Pertama, Diameter Pangkal Cabang, dan Jumlah Daun pada Semua umur amatan, NPK 16:16:16 berpengaruh pada pengamatan pada umur 56 Hari Setelah Tanam, kandungan dosis tanaman dengan Pupuk POC KOHE Kambing pupuk terbaik Pada P3 3 lter /plot, Interaksi dosis NPK 16:16:16 dan POC KOHE Kambing berpengaruh pada semua parameter pengamatan.Â Kata kunci: Cabai Merah, Pupuk NPK 16:16:16, POC Kohe Kambing, Pertumbuhan TanamanÂ